On the relation between the inertial coagulation and the amplitudal effect - H. CZYŻ (Archives of Acoustics)
The phenomenon of drift of small particles suspended in a gaseous medium in which the acoustic wave propagates, is known since long. In the present work, which refers to [7], we present an outline of a theory allowing for full interrelation of all quantities characterizing the particle, the medium and the acoustic field.